Digital Visualizer as an Aid-assisted Teaching in Anatomy - Senthil kumar.B1, Deepti Shastri2 , Samraj. T3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Innovative medical education technologies are used as alternate mode of teaching-learning ofanatomy to undergraduate students. As knowledge of anatomy helps students in their clinical area, effectiveinnovative teaching-learning tools need to be explored to build up their competency in anatomy.Aim: To find the outcome of application of digital visualizer in systematic teaching-learning of anatomy toundergraduate dental students.Materials and methods: A cross sectional study was undertaken among first year dental students studyingat Penang International Dental College, Salem, India. 50 students were divided in two groups. The groupswere subjected to conventional and aid-assisted teaching using digital visualizer in a cross-over design onseparate topics with comparable level of difficulty. Both groups were assessed by pre and post-test followedby feedback from them in reference to use of digital visualizer as aid in regular anatomy teaching-learningprocess.Results: Both the conventional and aid-assisted teaching showed significant changes in students pertainingto gaining of subject knowledge and the mean post-test score was found to be higher with the use of digitalvisualizer. The post-test scoring using digital visualize in both groups was higher in osteology teaching(10.21±0.76 & 10.39±0.83) and cadaver specimen demonstration (8.76±0.44 & 8.80±0.41). In the feedbackanalysis, majority of the students considered digital visualizer as an innovative aid for teaching-learning inanatomy.Conclusion: The use of medical educational technologies can assist as a comprehensive tool in regularteaching learning sessions. The study will be further continued for first year medical students of ourinstitution.